Cambridge encyclopedia of human evolution (Cambridge Univ. Press, 1992)
The book is a wide-ranging introduction to the human species that places modern humans in evolutionary perspective. Its content is divided into 10 parts. *) Part 1 presents patterns of primate evolution: the nature of evolution, classification and evolutionary relationships, non-human primates and conservation of primates. *) Part 2 presents the life of primates: body size and energy requirements, human adaptations to the physical environment, differences between the sexes, jaws and teeth, diets and guts, selecting and processing food, human diet and subsistence, primate locomotion and posture, human locomotion, primate reproduction, hormones and sexual behaviour, life-history patterns, human growth and development. *) Part 3 deals with the brain and language: Primate brains and senses, the human brain, vocal communication by non-human primates, biological aspects of language, human speech and language, language training of apes. *) Part 4 discusses the primate social organization: social behaviour and evolutionary theory, mating and parental care, home range and territory, smell as a signal, facial patterns as signals and masks. *) Part 5 delves into human evolution in a geological context: land movements and species disposal, climatic change in the past, methods of dating, fossil deposits and their investigation, reconstructing past environments. *) Part 6 provides the primate fossil record: the fossil history of primates, evolution of New World monkeys, evolution of Old World monkeys, evolution of apes, evolution of australopithecines, evolution of early humans. *) Part 7 presents primate genetics and evolution: principles of geneyics, genetic diversity in humans. *) Part 8 provides genetic clues of relatedness: chromosomal evolution in primates. *) Part 9 presents early human behaviour and ecology: the hominid way of life, evolution of human manipulation, tools - the paleolithic record, origine of agriculture, domestic of animals. *) Part 10 covers human populations, past and present: the dispersion of modern humans, people and disease, fertility control: past, present and future, tribal peoples in the modern world. the book end with a conclusion which presents the evolutionary future of humankind